الطاقة الإنتاجية ,الإنتاج الفعلي, الاستهلاك المنزلي للمياه النقية في مدينة الموصل - سحر عبدالجبار محمود (PROSPECTIVE RESEARCHES, 2023)
Sample survey conducted by the author shows that Mosul City uses around 243.000 cubic meter of purified water for domestic purposes. This quantity makes about 43% of total productive capacity (and output) of water purification. Stations are serving the city today (Nov. 2010). This means that around 67% of total productive capacity (and output) goes to other uses including commercial and institutional water on the one hand, and water leaks from water distribution system in the city, on the other. The author thinks that the present study, though limited in scope, paves the way for comprehensive study on the total quantity of purified water use (domestic, commercial, etc.) in Mosul city on the one hand, and the quantity of "water leaks'', on the other. The study results in a number of recommendations.